A REFLECTION OF SURAH AL ANBIYAA IN FRIDAY KHUTBAH : A CRITICAL DISCOURSE STUDY - Rosyida Ekawati (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2013)
Friday prayer is indeed a very important weekly occasion because it involves a large section of the Muslim community regardless of their social standing. The sermon (khutbah) is the opportunity to deliver the essential message of Islamand to remind the congregation of their mistakes and shortcomings. Only a right person is appointed for the job. The study used CDA approach by Norman Fairclough. The data taken from youtube that broadcast Friday Khutbah in English. From the study, it is found that in delivering his khutbah, the khatib cited the ayah from the Holy Quran, of course, in Arabic language, to make better understanding. It can be used to convince the jamaah that the khutbah really agree with the content of the Holy book Al Quran, the most comprehensive source book for Muslim. Besides, it was not only the jamaah who should follow the instruction of the khutbah but all people include the khatib, that is why the khatib used the personal pronoun ‘we’ instead of ‘you’ which refers only to the jamaah. Though the khatib has powerful in term of religious knowledge, he did not place himself over the jamaah.